THE EFFECT OF RETURN ON EQUITY ON COMPANY VALUE WITH THE INDEPENDENT BOARD OF COMMISSIONERS AND THE AUDIT COMMITTEE AS MODERATING VARIABLES - Achmad Daengs GS; Enny Istanti; Diana Zuhro; Retno Susanti; Sutini Sutini; Ruchan Sanusi; Syafi'i Syafi'i; Sutopo Sutopo; Ali Muhdor; Bramastyo Kusumonegoro (International Journal of Economics and Management Research, 2022)
The purpose of this study was to analyze financial performance as measured by Return on Equity (ROE) on firm value as measured by Tobin's Q as well as to analyze the Corporate Governance mechanism as a moderating variable. The aim of this research is to find empirical proof about (a) the influence of financial performance to firm value, (b) the influence of independent commissioners as moderating variable in the relationships between financial performance and firm value, (c) the influence of audit committee as moderating variable in relationships between financial performance and firm value. The sample of this research is mining firms which are listed on the Indonesia Stock Exchange (IDX) over 2008-2011. The research sample are 10 firms with 39 observations. To analyzed the data using software SPSS ver. 16.0.